Evaluating Telehealth Websites for Information Consistent with APA Guidelines for Telepsychology. Issue 2 (2nd April 2020) - Fiene, S. L.; Stark, K. S.; Kreiner, D. S.; Walker, T. R.
Abstract: The authors evaluated websites offering therapeutic telehealth services ( N  = 55) using a 38-item checklist based on the American Psychological Association's Guidelines for the Practice of Telepsychology ( APA Guidelines) to determine the extent that online service providers included such information on their websites. On average, the websites reviewed addressed only 39% of the checklist criteria. These findings are disconcerting and suggest most providers' websites do not include information that would help potential clients make informed decisions about online treatment. The authors urge more providers to consider offering telehealth services to increase the supply of qualified providers in response to growing consumer demand.